Human Endogenous Retroviruses and Their Putative Role in Pathogenesis of Alzheimer’s Disease, Inflammation, and Senescence - Patrycja Kozubek; Julia Kuźniar; Magdalena Czaja; Hanna Sitka; Urszula Kochman; Jerzy Leszek (Biomedicines)
The human endogenous retroviruses (HERVs) are ancient exogenous retroviruses that were embedded in the germline over 30 million years ago and underwent an endogenization process. They make up roughly 8% of the human genome. HERVs exhibit many physiological and non-physiological functions; for example, they play a role in the development of many diseases. They have been shown to affect carcinogenesis by modifying the expression of host genes through their functions as enhancers and promoters. Additionally, some molecules derived from HERVs may stimulate the immune system. Recently research has been focused on the effect of human endogenous retroviruses on the development of neurodegenerative diseases, including Alzheimer’s disease (AD), which is the most common cause of dementia. AD is also linked to a significant deterioration in quality of life. The article aims to highlight the potential role of HERVs in neurodegenerative diseases such as Alzheimer’s disease and senescence. Moreover, it is estimated that HERVs may be potential targets for diagnosis and therapy of AD.